Generation Z and its heroes - N. S. Evsegneeva (Вестник университета)
The article was prepared on the basis of the results of the sociological research “Social networks and electoral potential”. The research methods included conducting focus groups involving young people aged 17 to 25 and subsequent content analysis of the data obtained. The purpose of the survey was to identify the opinion of young people about the heroes of our time, the concept of heroism and heroic professions. The study is unique in its analysis of the blogosphere and bloggers from the point of view of contemporary heroism and the identification of the social networks role in this process. The results of the study showed that Generation Z is striving to acquire a social mission in their activities and the theme of heroism moves into the plane of everyday life: everyone can become a hero.